Competition in the Financial Sector and Financial Crises in a Business Cycle Model - Kopiec, Paweł (Central European Journal of Economic Modelling and Econometrics, 2023)
This theoretical work studies a dynamic general equilibrium model with the financial sector in which aggregate activity depends on the conditions of intermediaries’ balance sheets. This environment is used to demonstrate the business cycle consequences of changes in competition in the financial industry. On the one hand, a more competitive banking sector is associated with a higher average level of aggregate output. On the other hand, however, a less competitive financial industry increases financial and macroeconomic stability. This trade-off is present both in the short run and in the long run.